Should We Regularly Include Pulmonary Embolism in the Differential Diagnosis of Syncope?. Issue 3 (May 2017) - Pino, Alejandro; Zappetti, Dana
Abstract : Synopsis: In patients admitted to the hospital for a first episode of syncope, workup for pulmonary embolism should be included, despite alternative explanations for the syncopal episode. Pulmonary embolism was identified in nearly 1 of every 6 patients hospitalized for syncope. Source: Prandoni P, Lensing AW, Prins MH, et al. Prevalence of pulmonary embolism among patients hospitalized for syncope. N Engl J Med . 2016;375:1524–1531.